STRATEGI MUTU PENDIDIKAN KATOLIK MELALUI TRANSFORMASI MANAJEMEN KEMITRAAN ANTAR LEMBAGA PENDIDIKAN KATOLIK - Hamu, Fransiskus Janu (SEPAKAT-Jurnal Pastoral Kateketik, 2016)
The purpose of this paper is to examine the situation and condition of the Catholic educational institutions. This is done by a large number of opinions that compelled delivered community that the quality of Catholic schools is going lower so that people are not interested anymore to study at the Catholic school. It is opposite to diverse opinions about the existence of Catholic schools that rise the anxiety and a discussion among the Catholics. Through this writing, it is tried to seeks and find the root of the problems and then try to offer the step to solve.Â  Â From this research, it was found that many people recognize the quality of the Catholic School suffered a setback. Due to the poor quality of the present Catholic school, many societies are not interested to study in Catholic schools anymore. The low quality of the Catholic school is caused by the low quality of management system, educators, weak leadership style, and lack of facilities as well as the very limited funds for operation of the school. Therefore the requirement to perform the transformation management in total is an imperative that cannot be postponed any longer.